2022
DOI: 10.1002/ctm2.765
|View full text |Cite
|
Sign up to set email alerts
|

m6A hypomethylation of DNMT3B regulated by ALKBH5 promotes intervertebral disc degeneration via E4F1 deficiency

Abstract: Background The intervertebral disc (IVD) degeneration is the leading cause of low back pain, which accounts for a main cause of disability. N6‐methyladenosine (m6A) is the most abundant internal modification in eukaryotic messenger RNAs and is involved in various diseases and cellular processes by modulating mRNA fate. However, the critical role of m6A regulation in IVD degeneration remains unclear. Nucleus pulposus cell (NPC) senescence is critical for the progression of IVD degeneration. Here, we uncovered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 68 publications
(140 reference statements)
0
36
0
Order By: Relevance
“… 163 The ALKBH5 level is increased during IVDD and NPC senescence, and it removes m 6 A from the DNMT3B mRNAs, which limits the expression of the transcription factor E4F1 by methylating CpG islands at its promoter region and accelerates NPC senescence. 164 …”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“… 163 The ALKBH5 level is increased during IVDD and NPC senescence, and it removes m 6 A from the DNMT3B mRNAs, which limits the expression of the transcription factor E4F1 by methylating CpG islands at its promoter region and accelerates NPC senescence. 164 …”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“…Demonstrated that ALKBH5-mediated mRNA demethylation accelerated intervertebral disc (IVD) aging through ex vivo experiments. AlKBH5 caused disc aging and nucleus pulposus degeneration by demethylating DNMT3B transcripts Li et al (2022) . Found that in the nucleus pulposus of patients with disc degeneration, the mRNA content of MAT2A was lower than normal, while the mRNA of the demethylase metttl16 was higher.…”
Section: N6-methyladenosine and Bone Developmentmentioning
confidence: 99%
“…To date, increasing research have reported the connection between m 6 A and organ aging/cell senescence. However, most of them mainly focused on methyltransferase, such as METTL3/METTL14 ( Zhang J. et al, 2020 ; Wu et al, 2020 ; Liu et al, 2021 ; Chen et al, 2022 ), and the demethylases and readers were gradually concerned in recent years, including ALKBH5 ( Li et al, 2022a ), WTAP ( Li et al, 2022b ), IGF2BP2 ( Deng et al, 2021 ). Notedly, in reproductive aging, FTO has been shown to play the regulatory role ( Ding et al, 2018 ; Zhou L. et al, 2021 ; Jiang et al, 2021 ; Sun et al, 2021 ).…”
Section: M 6 a Methylation Modification In Female ...mentioning
confidence: 99%